THE USAGE OF WEB SEARCH ENGINES FOR THE KNOWLEDGE GAINING - Yajid, Mohd Shukri Ab; Azam, S.M. Ferdous; Sakinah (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the current analysis is to explore the usage of web engines for the sake of knowledge gaining and sharing. First this study used the appropriate research tools; applications and other related peripherals. Next mentioned are the research procedure elaboration and data sub-categorization explanation. Statistical analysis is applied to study the distribution of download speed and the relationship between the sizes of websites with download speed by applying the simple regression method (Hulth & Rydevik, 2011).